2019
DOI: 10.1002/lno.11174
|View full text |Cite
|
Sign up to set email alerts
|

Is the trophic diversity of marine benthic consumers decoupled from taxonomic and functional trait diversity? Isotopic niches of Arctic communities

Abstract: It is predicted that a diverse array of functional traits in species‐rich assemblages can lead to strong resource partitioning among coexisting species and moderate a wider spectrum of resource use. We compared two benthic communities in an Arctic fjord: a species‐rich community (in an outer basin) and an impoverished community (in a glacially impacted bay) and explored (1) if high species richness was translated into high functional trait richness and (2) if high taxonomic and functional diversity promoted hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 57 publications
0
16
0
Order By: Relevance
“…Although the sampled stations in this study cover only a part of the fjord's length, significant gradients of salinity (Paulsen et al 2017; Sejr et al 2017), organic matter quality (Bridier et al 2019), and primary production (Meire et al 2017) have been reported between the same stations. In a similar spatial and salinity gradient of Hornsund (Svalbard), Włodarska‐Kowalczuk et al (2019) highlighted a clear δ 13 C shift between benthic food webs of inner and outer fjords, which they attributed to different relative contributions of various organic matter sources. The absence of such a trend in Young Sound may signify that the organic matter pool fueling inner and outer communities is minimally affected by environmental gradients.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Although the sampled stations in this study cover only a part of the fjord's length, significant gradients of salinity (Paulsen et al 2017; Sejr et al 2017), organic matter quality (Bridier et al 2019), and primary production (Meire et al 2017) have been reported between the same stations. In a similar spatial and salinity gradient of Hornsund (Svalbard), Włodarska‐Kowalczuk et al (2019) highlighted a clear δ 13 C shift between benthic food webs of inner and outer fjords, which they attributed to different relative contributions of various organic matter sources. The absence of such a trend in Young Sound may signify that the organic matter pool fueling inner and outer communities is minimally affected by environmental gradients.…”
Section: Discussionmentioning
confidence: 95%
“…The relatively low degradation of settled particles in polar ecosystems usually leads to the accumulation of a persistent sediment food bank of labile detritus (Smith et al 2006; Mincks et al 2008). The resuspension of these labile detritus (through bottom currents or bioturbation) has a considerable importance for arctic benthic food webs facing periods of low food availability by providing an alternative food source for suspension feeders (Smith et al 2006; Włodarska‐Kowalczuk et al 2019). We hypothesize that such resuspension events in Young Sound might thus partly increase the temporal stability and spatial homogeneity of the benthic food web in the face of strong spatiotemporal variations in primary production and organic matter quality (Meire et al 2017; Bridier et al 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, during both seasons, the TA and SEAc of fish assemblages in the South Sea exhibited wider ranges than those in the East Sea. Such spatial differences in the isotopic niche areas may mostly result from the different environmental conditions and/or species compositions that can alter the trophic relationships within the community [53,54]. Our results also suggest that the spatial differences in the TA and SEAc may be associated with the regional distinction in the fish community interacting with different environmental conditions.…”
Section: Discussionmentioning
confidence: 66%